REVERSE ENGINEERING: DISMANTLING AND CUSTOMIZING FOR THE NEW GLOBAL MEDIA ECOLOGY. - Zimmermann, Patricia R. (Afterimage)
The article examines how reverse engineering dismantles and customizes technologies for the new global media ecology. It says that the engineering offers a way to conceptualize a radical media insurgency in these new media ecologies. Vietnamese recycled the metal from downed U.S. warplanes and made traps to fight U.S. ground troops.